2014
DOI: 10.1002/etc.2555
|View full text |Cite
|
Sign up to set email alerts
|

Developmental impairment in eurasian dipper nestlings exposed to urban stream pollutants

Abstract: Avian studies of endocrine disruption traditionally have focused on reproductive impairment, given that many environmental contaminants affect sex steroid hormones. There is also increasing interest in altered thyroid function, and associated early development, particularly in altricial species with extended developmental windows. Both types of effect are relevant under the complex pollutant conditions created in streams draining urban areas, but case studies are scarce. Therefore, the authors measured breedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 71 publications
(103 reference statements)
1
15
0
Order By: Relevance
“…The findings of the present study support and develop our understanding of the effects of PBDEs on thyroid hormones in young birds . In the present study, the controlled exposure of kestrels to PBDEs in a laboratory setting allowed for identification of thyroidal effects that can be attributed to PBDEs in relative isolation, without the confounding influence of exposure to multiple thyroid hormone–disrupting compounds (e.g., polychlorinated biphenyls) experienced by wild birds (e.g., Morrissey et al ). We found that embryonic exposure by maternal transfer to the technical PBDE mixture DE‐71 altered thyroid gland function and circulating thyroid hormones in female, but not male, kestrel nestlings during the period of rapid growth.…”
Section: Discussionsupporting
confidence: 75%
“…The findings of the present study support and develop our understanding of the effects of PBDEs on thyroid hormones in young birds . In the present study, the controlled exposure of kestrels to PBDEs in a laboratory setting allowed for identification of thyroidal effects that can be attributed to PBDEs in relative isolation, without the confounding influence of exposure to multiple thyroid hormone–disrupting compounds (e.g., polychlorinated biphenyls) experienced by wild birds (e.g., Morrissey et al ). We found that embryonic exposure by maternal transfer to the technical PBDE mixture DE‐71 altered thyroid gland function and circulating thyroid hormones in female, but not male, kestrel nestlings during the period of rapid growth.…”
Section: Discussionsupporting
confidence: 75%
“…Six comparisons report only results on first clutches, and four comparisons include both first and second clutches. In these studies (Mennechez & Clergeau, ; Minias, ; Morrissey et al., ; and Newhouse et al., ) no differences in the probability of laying a second clutch is reported between urban and rural populations, and trends along the urbanization gradient are similar for first and second clutches. In addition, Bailly et al.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, some authors have observed that the high concentration of organochlorines (OGC) in tissues of northern Baltic Sea nestlings seagulls found dead can enhance the septicemia risk (Hario et al 2004). OGCs decrease the ability of the immune system to respond correctly to infections (Hario et al 2004, Morrissey et al 2014. It should be emphasized that the southernmost region of RS, where most of those birds of this work came from, is a well-developed agricultural region with large rice and soybeans crops.…”
Section: Discussionmentioning
confidence: 98%